Ambient Ammonia Electrosynthesis: Dramatically Enhanced Ambient Ammonia Electrosynthesis Performance by In‐Operando Created Li–S Interactions on MoS2 Electrocatalyst (Adv. Energy Mater. 14/2019). Issue 14 (10th April 2019) - Liu, Yanyan; Han, Miaomiao; Xiong, Qizhong; Zhang, Shengbo; Zhao, Cuijiao; Gong, Wanbing; Wang, Guozhong; Zhang, Haimin; Zhao, Huijun
Abstract : In article number1803935, Haimin Zhang, Huijun Zhao and co‐workers enhance the ambient NH3 electrosynthesis performance of MoS2 dramatically by in‐operando created Li–S interactions through effectively suppressed HER activity at S‐edge/Mo‐edge sites, and simultaneously increased N2 adsorption capability and boosted NRR catalytic activity on Mo‐edge sites.